CLINICAL EVALUATION OF ELECTRODIAGNOSTICALLY VERIFIED CARPAL TUNNEL SYNDROME - Breda Jesenšek Papež; Zmago Turk (Zdravniški Vestnik, 2004)
Background. The aim of the research was a clinical evaluation of a group of people with confirmed carpal tunnel syndrome and setting of useful instructions for daily use. Methods. Prospective study includes 70 potential patients suffering from carpal tunnel syndrome. By using electrodiagnostics, the diagnosis could be confirmed with only 30 patients that were checked up. These were clinically evaluated on the following criteria: anamnesis, Katz-hand diagram, symptoms and signs. Results. The study found a higher percentage of carpal tunnel syndrome in women. The difference between women and men in this respect is statistically significant (p < 0.05). In most cases, both hand are afflicted or, in the case of just one hand, usually the dominant one (20 patients [66.6%]). At an average, the problems lasted for 1184 days. The average age was 51.13 years. 22 people (73.3%) had coincident problems with the neck and shoulder. Typical symptoms were tingling, pain and awakening. In 66% (33 hands) disturbed sensory functions were registered: hypo sensibility 52%, hyper sensibility 14%. The first place of the provocative diagnostically tests takes Phalen (72% – 36 arms) followed by Tinel (70% – 35 arms), reverse Phalen 54% and tethered median nerve stress test 46%. The Katz diagram is not of a mentionable diagnostic value according to our experience. Conclusions. The typical carpal tunnel syndrome can be clinically identified by a precise test performance, observation and with help of anamnesis. For the confirmation of the diagnosis and planning of the treatment the electrodiagnostic test is used.